WORKSHOP E-LEARNING GOOGLE CLASSROOM DAN VIDEO PEMBELAJARAN PADA SMP N 35 PEKANBARU - Yoyon Efendi; Lusiana Lusiana; Rometdo Muzawi; Rini Yanti; Syahrul Imardi (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2021)
Learning problems are often the reason teachers do not provide material in class optimally. Like condition COVID 19 at this time, apart from that, for various reasons, such as the teacher having a meeting, the city office is an obstacle for teachers to deliver material at school, even students roaming around and fighting in class. An effective and efficient learning media is needed for teachers to continue delivering material even under any circumstances. Learning using Google Classroom, one way to face the challenges of the technology world in education through learning media. Besides that, the making of instructional videos will increase the creativity of teachers to make interesting and interactive teaching materials. This workshop was attended by 21 teachers from SMP N 35 Pekanbaru. After going through the pre-test and post-test, there was an increase in the knowledge and skills of teachers in managing classes on Google Classroom and learning videos. This workshop can be a provision for teaching and learning activities at school and outside of school.